2018
DOI: 10.1007/978-3-319-93843-1_44
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Kit-Building of Concept Map to Share Each Other’s Understanding as Preparation for Collaboration

Abstract: Collaborative learning is an active teaching and learning strategy, in which learners who give each other elaborated explanations can learn most. However, it is difficult for learners to explain their own understanding elaborately in collaborative learning. In this study, we propose a collaborative use of a Kit-Build concept map (KB map) called "Reciprocal KB map". In a Reciprocal KB map for a pair discussion, at first, the two participants make their own concept maps expressing their comprehension. Then, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A possible factor contributing to better group outcomes is the interaction during discourse. The initial study of RKB presents that the pairs in the experimental groups demonstrate more exploratory talk when they discuss each other's ideas, compared to the pairs who were not using the system (Wunnasri et al 2018a(Wunnasri et al , 2018b. Exploratory talk is a type of talk in which partners engage in each other's ideas critically but constructively (Mercer 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible factor contributing to better group outcomes is the interaction during discourse. The initial study of RKB presents that the pairs in the experimental groups demonstrate more exploratory talk when they discuss each other's ideas, compared to the pairs who were not using the system (Wunnasri et al 2018a(Wunnasri et al , 2018b. Exploratory talk is a type of talk in which partners engage in each other's ideas critically but constructively (Mercer 1996).…”
Section: Discussionmentioning
confidence: 99%
“…While creating an individual map is a method to express own understanding, the reconstruction activity is a method to understand the partner's point of view. Ideas exchange through the reconstruction of concept map components from a partner's map, and the discussion of difference maps could encourage understanding of the partner's representation (Wunnasri et al 2018b). Comprehension of partner representation becomes visible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strategy to foster knowledge convergence during collaboration is by nurturing group members to apply the knowledge available to them, both shared and unshared knowledge. The current study employs the Reciprocal Kit Build (RKB) approach, as introduced by [10], [11], to allow students to externalize their thinking, exchange knowledge through reconstruction, and discuss group members' similar and dissimilar areas of understanding, with the support of a difference map. The approach engages group members to operate on boundary objects; i.e., the map structures and components.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the RKB approach promotes productive discussion [10], [11]. Unlike those studies, after following the proposed activity, we ask the students to build an integrated map that represents their understanding as a group.…”
Section: Introductionmentioning
confidence: 99%